Mediation role of residential density on the association between perceived environmental factors and active commuting to school in Brazilian adolescents - Arieli Fernandes Dias; Anelise Reis Gaya; Caroline Brand; Alex Antonio Florindo; Emilio Villa-González; Antonio García-Hermoso; Jorge Mota; Adroaldo Cezar Araujo Gaya (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2021)
Abstract: The objective of this study was to verify whether residential density and connectivity between streets are mediators on the association between perceived environmental factors and active commuting to school (ACS) in Brazilian adolescents. This is a cross-sectional study with a random sample of 1,130 adolescents (52.7% girls) aged between 14 to 20 years, from Porto Alegre, Rio Grande do Sul State, Brazil. Adolescents' self-reported their usual mode of commuting to and from school using a questionnaire and the perceived environmental attributes by Neighborhood Environment Walkability Scale for Youth (NEWS-Y). Residential density and connectivity between streets were measured by gographic information systems (GIS), within 1km road network buffers around the participant's residential address. Regression models were fitted according to mediation analyses procedures. The results showed that residential density is a mediator on the association between ACS and perceived environmental factors, including land-use mix diversity (IE = 0.114; 95%CI: 0.130, 0.311; 32% mediation), neighborhood recreation facilities (IE = 0.064; 95%CI: 0.034, 0.105; 15% mediation), and access to services (IE = 0.045; 95%CI: 0.006, 0.104; 14% mediation). Connectivity between streets did not correlate with ACS, thus it was not tested in the mediation model. In conclusion, residential density is a mediator on the relationship between perceived environmental factors and ACS.